Slow, deep breathing intervention improved symptoms and altered rectal sensitivity in patients with constipation-predominant irritable bowel syndrome - Liu, Jie; Lv, Chaolan; Wang, Wei; Huang, Yizhou; Wang, Bo; Tian, Jiashuang; Sun, Chenyu; Yu, Yue (Frontiers in Neuroscience, 2022)
Background: Limited treatment options have been shown to alter the natural course of irritable bowel syndrome(IBS). Slow, deep breathing (SDB) is a common pain self-management intervention. This pilot study aimed to explore the impact of SDB on measures of autonomic and anorectal functions as well as patient-reported symptoms in constipation-IBS (IBS-C). Methods: Eighty-five IBS-C patients were enrolled in this study and randomly assigned to the experimental group (Group A, n = 42) and the control group (Group B, n = 43). SDB was conducted at six breathing cycles per minute. All subjects underwent high-resolution anorectal manometry and completed the standardized IBS symptom severity system (IBS-SSS) questionnaire. Meanwhile, changes in stool consistency, weekly frequency of complete spontaneous bowel movements (CSBMs), and weekly frequency of spontaneous bowel movements (SBMs) were recorded. All IBS-C patients received electrocardiogram recordings for heart rate variability (HRV) analysis. Results: At baseline, no differences were found between Groups A and B. The IBS-SSS score and its five sub-scores of Group B patients were significantly higher at week 6 than those of Group A patients (all p < 0.001). Furthermore, compared with Group B patients, Group A patients had a significantly higher threshold volume for the first sensation (p < 0.001), desire to defecate (p = 0.017), and maximum tolerable volume (p = 0.018) at week 6 of the SDB treatment. We also noted significant improvements in weekly SBM frequencies (p < 0.001), and weekly CSBM frequencies (p = 0.018) of Group A patients at week 6 when compared with Group B patients. Finally, the corrected high frequency (HF) of Group A patients was significantly higher than the HF of Group B patients at week 3 (p < 0.001) and at week 6 (p < 0.001). Likewise, patients in Group A had a significantly higher root mean square of the successive differences than that of patients in Group B at week 3 (p < 0.001) and at week 6 (p < 0.001). Conclusions: We found that a six-week SDB intervention improved symptoms and altered rectal sensation in IBS-C patients, which might be due to mechanisms involving autonomic responses.